Tailoring engineered cementitious composite with emulsified asphalt for high damping - Ma, Hui (2020)
Cement asphalt (CA) mortar has been widely used as cushion layer between the concrete roadbed and track slab for vibration absorption in high-speed railways (HSR). However, premature cracking of CA has been recognized as a critical safety problem during HSR operation. There is a need for developing more durable materials with similar damping ability and vibration absorption characteristics as CA mortar. This paper reports the development of emulsified asphalt (EA) modified Engineered cementitious composite (EA-ECC) with favorable damping property, which may be used as vibration absorbing layer material. The mechanical properties, including compressive strength, tensile stress-strain relation and dynamic mechanical properties of EA-ECCs were investigated. It is found that the desirable higher loss modulus and loss factor are accompanied by lower compressive and tensile strength with increase of EA dosage. Conversely, the deformation capacity of EA-ECCs shows an opposite trend due to favorable change in interfacial properties. In addition, with increasing test temperature, the material also shows a trend similar to the addition of EA. Change of microstructures of EA-ECCs were also observed through scanning electron microscope (SEM) imaging. It is concluded that incorporating EA significantly improves the tensile ductility and energy dissipation ability of ECC materials. Increase of 210 times in tensile ductility and similar loss factor are demonstrated when compared with those of CA with similar EA dosage.